A Preliminary Investigation of the Views of People With Parkinson's (With and Without Psychosis) and Caregivers on Participating in Clinical Trials During the Covid-19 Pandemic: An Online Survey - McGoohan, Katie; Amjad, Anneesa; Ratcliffe, Natasha; Bhattacharyya, Sagnik; Granville, Gillian; Sullivan, Matthew; Gosden, Lesley; Aarsland, Dag; Chaudhuri, K. Ray; ffytche, Dominic; Ballard, Clive; Velayudhan, Latha (Frontiers in Psychiatry, 2020)
Background: The coronavirus pandemic is having a profound impact on non-COVID-19 related research, including the delivery of clinical trials for patients with Parkinson’s disease Objectives: A preliminary investigation to explore the views of Parkinson’s disease (PD) patients, with and without experience of psychosis symptoms, and carers on the resumption of clinical research and adaptations to trials in light of COVID-19. Methods: An anonymous self-administered online survey was completed by 30 PD patients and 6 family members/carers via the Parkinson’s UK Research Support Network to explore current perceptions on taking part in PD research and how a planned clinical trial for psychosis in PD may be adapted so participants feel safe. Results: 91% of respondents were enthusiastic about the continuation of non-COVID-19 related research as long as certain safety measures were in place. 94% stated that they would be happy to complete assessments virtually. However, they noted that care should be taken to ensure that this does not exclude participants, particularly those with more advanced PD who may require assistance using portable electronic devices. Regular and supportive communication from the research team was also seen as important for maintaining the psychological wellbeing of participants while taking part in the trial. Conclusions: In the era of COVID-19 pandemic, standard approaches will have to be modified and rapid adoption of virtual assessments will be critical for the continuation of clinical research. It is important that alongside the traditional methods, new tools are developed, and older ones validated for virtual assessments, to allow safe and comprehensive assessments vital for ongoing research in people with Parkinson’s.